A 60-GHz Wideband High-Efficiency Circularly Polarized Dual-Coil Antenna Array - Jun Xiao; Qi Gan; Zihang Ye; Chong-Zhi Han; Tongyu Ding; Qiubo Ye (Sensors)
A wideband high-efficiency circularly polarized (CP) dual-coil antenna array is presented for 60-GHz applications in this letter. The proposed CP dual-coil antenna is composed of a resonant substrate-integrated cavity (SIC) and a pair of centrally symmetrical coils, which are fed differentially by a substrate-integrated waveguide (SIW) coupling slot. A novel sequential rotation feeding technique is introduced to enhance the axial ratio (AR) and impedance bandwidths of both the 2 × 2 subarray and the 4 × 4 array. The proposed feeding network significantly improves radiation efficiency. The measured results of the fabricated prototype indicate that the proposed array achieves an impedance bandwidth of 20.8% (54.6–67.3 GHz) for |S11| ≤ −10 dB, a 3-dB AR bandwidth of 21.5% (54–67 GHz), a high radiation efficiency of 96.6%, and a peak gain reaching 19.3 dBic at 58 GHz. The proposed circularly polarized (CP) antenna element and array design stand out as strong contenders for 60-GHz wireless applications.